2019
DOI: 10.1177/2042098619854007
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide as a prokinetic agent for diabetic gastroparesis: revisiting the risk of Parkinsonism

Abstract: Background: Metoclopramide is used to relieve gastrointestinal symptoms, however, it could cause adverse reactions of motor disorders. The aim of this study was to investigate whether metoclopramide treatment has a duration–response or dose–response effect and to estimate the risk of developing Parkinsonism following different and specific durations of treatment. Methods: A cohort study of newly diagnosed type 2 diabetes mellitus in 45- to 79-year-old patients, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, the adverse effects of the drug continue to be reported. For example, a study of 34,685 diabetic patients treated with metoclopramide found that the risk of Parkinson’s syndrome increased with the duration of treatment, regardless of whether or not the drug was used for more than 3 months [ 70 ]. In fact, in 2009, the USA Food and Drug Administration (FDA) issued a warning that metoclopramide use may lead to irreversible delayed-onset dyskinesia [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the adverse effects of the drug continue to be reported. For example, a study of 34,685 diabetic patients treated with metoclopramide found that the risk of Parkinson’s syndrome increased with the duration of treatment, regardless of whether or not the drug was used for more than 3 months [ 70 ]. In fact, in 2009, the USA Food and Drug Administration (FDA) issued a warning that metoclopramide use may lead to irreversible delayed-onset dyskinesia [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these drugs e.g. domperidone, have been banned in the USA, Canada, and other counties [16][17][18][19][20]. Thus, it is crucial to identify novel candidate drugs for treating FD.…”
Section: Discussionmentioning
confidence: 99%
“…Debido a que atraviesa la barrera hematoencefálica se deben considerar sus efectos adversos extrapiramidales (18) como el parkinsonismo, así como también tener en cuenta que puede producir discinesia y acatisia (29). Por ello se recomienda un monitoreo cercano para detectar tempranamente el parkinsonismo y otros efectos adversos medicamentosos (30).…”
Section: Procinéticosunclassified